Pregnancy complications after allogeneic hematopoietic stem cells transplantation: Focus on the placenta. (February 2023) - Gazzo, Irene; Massarotti, Claudia; Chiodi, Sandra; Spinelli, Simonetta; Gualandi, Francesca; Passamonti, Ubaldo; Fulcheri, Ezio; Angelucci, Emanuele; Cagnacci, Angelo
Abstract: Introduction: hematopoietic stem cells transplantation (HSCT) is a treatment option for malignant and non-malignant haematological diseases. Because of the improved survival rates and the more widespread use of reproductive technologies in the last two decades, the number of patients who conceive is increasing while the pathogenesis of some obstetrical complications observed is not yet fully clarified. Methods: we present complete data about two pregnancies in women who had previously undergone HSTC, with conditioning regimen including total body irradiation. One pregnancy is spontaneous and one after oocytes donation. Results: In both pregnancies we observed relevant intrauterine growth retardation, attributable to a deficit in implantation and placentation. Ultrasound and histological data point to a defective placenta development, possibly sustained by uterine vessel damage caused by irradiation. A deeper understanding of factors influencing placentation post total body irradiation and HSCT, including the possible role of donor's sex and graft versus host disease, is pivotal to improve pregnancy outcomes in this specific population. Highlights: The etiopathogenesis of obstetrics complications after hematopoietic stem cells transplantation is yet not clarified. We present two cases, one spontaneous pregnancy and one after oocyte donation. There is evidence of poor placentation leading to precocious symmetric growth retardation. Placental hyperplasia and adaptive modifications to chronic hypoxia were observed. Previous irradiation and imbalanced immune reaction of graft cells may play a role.